Construção de práticas de ensino de leitura: com a palavra o professor - (:unkn) unknown (Universidade Federal de Goiás, 2013)
Give voice to the teacher tell how he has been building his practices of teaching reading, describing his view, inserted in a context where most studies imply that the difficulty of building readership is in the teaching / learning of reading, putting as the author of the failure of this teaching is the goal of this work. For this, we seek to raise aspects of the experience of three teachers working in the 5th grade of Elementary School, trying to identify the needs and difficulties faced in teaching; analyze the structural conditions and materials, which are offered for teachers to build their teaching practices read and observe their plans with respect to the work with reading in the classroom. We assume that, as emphasizes Borges da Silva (2001), if the academic work aims to contribute to an improvement of basic education, it is essential to consider the needs of knowledge and counterarguments teacher. The research was conducted within the qualitative paradigm, from a socio-historical approach, with a view to study the processes that involve research, going beyond just an end product. The process of data collection, following the tradition of qualitative research (LÜDKE and ANDRÉ, 1986), included the semistructured interview, dialogued, and observation of teachers' planning. The literature review comprised studies on reading as the construction of meanings, the relationship of teaching reading literacy in the student and construction practices of reading instruction teacher training. The research has revealed a reality of distance between what is preached in the laws of education and what is accomplished in practice, which makes it difficult for teachers able, alone, to leverage the quality of public education. Teachers find themselves in a scenario that is being blamed for the difficulty in forming critical readers and proficient. Claim that, in addition to its responsibilities as the professional who should lead the process of teaching and learning, the government must assert his speech in favor of investments in education resources, it is for the school management to break with a practice dedicated to serve the interests capital, omitting the function that should play as contributors to the achievement of successful teaching in the public schools, and to exercise a function of partakers in conducting the activities of the school. We note that the hours activities, work context, the pedagogical orientations and school management are configured in a tangle of obstacles for the teacher fight for better working conditions and a really effective teaching. We hope that this study will contribute to the strengthening and consolidation of prioritizing future work to give voice to teachers, at the expense of research which focuses on studies of their practices. This is because the voice of those professionals, showed us the need to keep rethinking the lonely context job in which they operate, and that has influenced negatively in building their practices of teaching reading
Keywords: Professor; Práticas de ensino; Leitura; Teacher; Teaching practices; Reading; PLANEJAMENTO E AVALIACAO EDUCACIONAL::POLITICA EDUCACIONAL